Turkey’s Shift to Green Energy and Search for Hydrocarbons - Mehmet, Özay; Yorucu, Vedat (Springer, 2020)
Turkey is following as two-track policy in its energy policy. It is rapidly shifting to renewable energy in parallel with Energy Transformation as a medium-term policy objective, investing heavily in solar, wind and nuclear energy, while rapidly liberalizing the energy market. © 2020, Springer Nature Switzerland AG.
Keywords: Energy management; Energy resources; Energy markets; Energy transformation; Green energy; Medium term; Policy objectives; Renewable energies; Energy policy